Investigating the Environmental and the Energy Saving Behavior among School Principals through Classification Algorithms - Ntanos, Stamatios; Kyriakopoulos, Grigorios L.; Anagnostopoulos, Theodoros; Xanthopoulos, Theodoros; Kytagias, Christos; Drosos, Dimitrios (International Journal of Renewable Energy Development, 2022)
Buildings are a significant energy consumption point since they account for 40% of the total energy demand and around 1/3 of greenhouse gas emissions. Energy-saving measures applied in the residential sector have led to a reduction in energy consumption during the last decade. On the contrary, such measures have not been widely applied in school buildings, although education is the second-largest energy consumer in the service sector. This paper aims to assess school principals' perceptions concerning energy saving and the environment since they are responsible for promoting energy-saving measures and investments and inspiring students and school personnel towards environmentally friendly behavior. Using survey data from Greek schools, we applied predictive classification models to locate the most critical variables that drive principals' perceptions of energy upgrading and energy-saving actions at school. Results revealed that the positive environmental perceptions of principals, the level of knowledge on Renewable Energy Sources (RES) and the active energy-saving behavior are related to energy-saving actions and energy upgrading in school environment. Furthermore, the creation of more RES oriented courses is related to positive energy-saving behavior and actions. Thus, emphasis should be put on educating and informing the school principals concerning RES technologies and energy-saving options since they are critical players in applying energy-saving measures in school buildings